Association of the relationship between nutritional status and certain biochemical parameters in obese children - Ozcelik-Ersu, Dilek; Kızıltan, Gul (Progress in Nutrition, 2021)
The prevalence of childhood obesity is increasing globally. Adiposity is more concentrated in subcutaneous tissue in women and visceral fat tissue in men. Abdominal obesity is more commonly associated with metabolic diseases in men. The results showed that the mean BMIz scores of boys was higher than girls, but total body fat was lower than girls. Total body fat free mass, water and muscle mass were higher in boys than girls. It was determined that children aged 10-17 years consumed fatty and sugary snacks and sugary drinks at school. Food consumption containing the carbohydrate, fat, saturated fat and cholesterol were higher in boys than girls. As a result, it was thought that it would be more beneficial and reliable to use anthropometric methods showing body composition together with BMI zscore while evaluating body weight in adolescents. While nutritional counseling, it may be beneficial to consider that the energy and nutrient requirements of male adolescent individuals and their daily food consumption are higher than girls. When the results of the study are evaluated, we mention that it would be appropriate to evaluate girls more carefully in terms of iron deficiency anemia and diseases such as insulin resistance and diabetes.